Biofunctional nanomaterials based on ultra fine silica, protein and aminocarbohydrates - Galagan, N.P.; Klymenko, N.Y.; Orel, I.L.; Novikova, E.A.; Turov, V.V. (Вiopolymers and Cell, 2010)
Aim. Investigation of adsorptive interactions of N-acetyl-D-glucosamine (GlcNAc) and N-acetylneuraminic acid (NANA) with ultra fine silica (UFS) modified by protein bovine serum albumin (BSA). Methods. Adsorption, IR-, 1H NMR- and laser Doppler spectroscopy. Results. Conditions for obtaining bionanocomposites (BNC) UFS/GlcNAc, UFS/BSA/GlcNAc and UFS/BSA/NANA are developed. Conclusions. Impellent ability of deconservated bovine gametes decreased in the presence of BNC after adsorptive fastening of protein on UFS surface. The 1H NMR spectroscopy data proved that interaction of GlcNAc with protein was accompanied by essential dehydratation of protein molecules.